2014
DOI: 10.1590/0101-60830000041114
|View full text |Cite
|
Sign up to set email alerts
|

Learning and memory and its relationship with the lateralization of epileptic focus in subjects with temporal lobe epilepsy

Abstract: Background: In medial temporal lobe epilepsy (MTLE), previous studies addressing the hemispheric laterality of epileptogenic focus and its relationship with learning and memory processes have reported controversial findings. Objective: To compare the performance of MTLE patients according to the location of the epileptogenic focus on the left (MTLEL) or right temporal lobe (MTLER) on tasks of episodic learning and memory for verbal and visual content. Methods: One hundred patients with MTLEL and one hundred pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…LHI was impaired in relation to non-LHI in both UC and CC, with sensitivity and specificity above 70%. The findings from the present study agree with those of studies that used the narrative as a whole unit, and verbal inputs and outputs [6][7][8]10,12,20,22 , except that the left-lateralization pattern extended beyond the temporal lobe in this study. Also in line with the present findings, concerning the input, activation that was more left-lateralized was previously observed in functional studies for reading than for listening comprehension 13,21 ; and, concerning the output, a UC: uncued condition; CC: cued condition; LHI: patients with left hemisphere injury; RHI: patients with right hemisphere injury; HP: healthy participants.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…LHI was impaired in relation to non-LHI in both UC and CC, with sensitivity and specificity above 70%. The findings from the present study agree with those of studies that used the narrative as a whole unit, and verbal inputs and outputs [6][7][8]10,12,20,22 , except that the left-lateralization pattern extended beyond the temporal lobe in this study. Also in line with the present findings, concerning the input, activation that was more left-lateralized was previously observed in functional studies for reading than for listening comprehension 13,21 ; and, concerning the output, a UC: uncued condition; CC: cued condition; LHI: patients with left hemisphere injury; RHI: patients with right hemisphere injury; HP: healthy participants.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, since narrative-specificity in brain function may arise at a hemispheric rather than at a regional level 4 , there is a need for validity studies on the role of cerebral laterality of injury in story comprehension and recall, which have been poorly investigated at a hemispheric level. This need arises also in view of the contradictory results regarding laterality and narrative processing, not only from studies on patients with brain impairments 3,6 , and especially on those with temporal lobe epilepsy [7][8][9][10][11][12] , but also from functional or anatomical studies on healthy subjects 4,5,[13][14][15][16][17][18][19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are varying studies on the cognitive and psychological deficits associated with epilepsy. Studies have revealed that epileptic children are susceptible to severe deficits in memory [9,10,11,12,13,14] and academic achievement [15,16] compared to healthy control group. Severe psychological deficits have also been found among epileptic children compared to healthy control group [17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%